7C.02: TRAINING AND ENVIRONMENTAL ENRICHMENT TO COUNTERACT COGNITIVE DECLINE. (June 2015) - Stea, F.; Bruno, R.; Ghiadoni, L.; Faita, F.; Di Lascio, N.; Del Turco, S.; Maffei, L.; Tognoni, G.; Taddei, S.; Picano, E.; Sicari, R.
Abstract : Objective: Physical activity is beneficial to vascular health; on the other hand, vascular damage is associated with cognitive impairment. Both physical activity and a cognitively stimulating environment are known to delay the onset of dementia. The Train The Brain study evaluates the effectiveness of a comprehensive program of physical training and mental activity in delaying cognitive decline in elderly people with mild cognitive impairment, at the same time investigating the relationship between physical, vascular, neurological, and cognitive fitness Design and method: Elders age 65–89 were recruited with the help of family physicians and territorial services. All participants underwent a neurological and cardiologic evaluation. In the vascular study, carotid pressure was measured with the SphygmoCor system (AtCor, Australia); longitudinal ultrasound scans of the common carotid were performed and 10-second video clips were recorded to be analyzed offline through the Cardiovascular Suite software (Quipu srl, Italy), with the computation of diameter, intima-media thickness, wall cross-sectional area, distensibility coefficient, compliance, stiffness, and elastic modulus. Subjects classified as mild cognitive impairment at the neurological examination were randomized either to standard care, or a 7-month program of physical training and environmental stimulation (lectures, games, music, social activities) three hours a week. The evaluation was then repeated. Results: Data were obtained for 57 patients who underwent training (T) and 30 controls (C). The only significant difference at baseline was in the distensibility coefficient (p = 0.045). Figure. No caption available. Vessel diameter increased in C and decreased in T; distensibility decreased in C; all carotid parameters were influenced by the combination of time and treatment, in a diverging trend, at a statistically significant level, while there was no effect on pressure. Introducing arterial pressures as covariates did not affect the findings. Conclusions: There was a significant difference in behavior in time of the two groups as for vessel enlargement, wall thickening and arterial stiffening. The proposed program of physical training and environmental enrichening seems to oppose the typical harmful effects of aging on the wall of the common carotid in elderly people with mild cognitive impairment.